2015
DOI: 10.5535/arm.2015.39.1.10
|View full text |Cite
|
Sign up to set email alerts
|

Correlation of Foot Posture Index With Plantar Pressure and Radiographic Measurements in Pediatric Flatfoot

Abstract: ObjectiveTo investigate the correlation between the Foot Posture Index (FPI) (including talar head palpation, curvature at the lateral malleoli, inversion/eversion of the calcaneus, talonavicular bulging, congruence of the medical longitudinal arch, and abduction/adduction of the forefoot on the rare foot), plantar pressure distribution, and pediatric flatfoot radiographic findings.MethodsNineteen children with flatfoot (age, 9.32±2.67 years) were included as the study group. Eight segments of plantar pressure… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
34
1
7

Year Published

2017
2017
2022
2022

Publication Types

Select...
5
3

Relationship

0
8

Authors

Journals

citations
Cited by 54 publications
(43 citation statements)
references
References 27 publications
1
34
1
7
Order By: Relevance
“…A study of 187 children found both the FPI and radiographic measures to be useful for evaluating flat feet; however, our results found that footprint measures are only valid for the paediatric flat foot (planus), with no clear association for either high‐arch (cavus) or normal‐arch (rectus) feet. Hence, footprint and foot posture measures potentially measure different aspects of the foot structure.…”
Section: Discussioncontrasting
confidence: 72%
See 2 more Smart Citations
“…A study of 187 children found both the FPI and radiographic measures to be useful for evaluating flat feet; however, our results found that footprint measures are only valid for the paediatric flat foot (planus), with no clear association for either high‐arch (cavus) or normal‐arch (rectus) feet. Hence, footprint and foot posture measures potentially measure different aspects of the foot structure.…”
Section: Discussioncontrasting
confidence: 72%
“…showed a correlation between the FPI and plantar pressure, concluding that the FPI and radiography are both useful tools to evaluate paediatric flat foot. This sample included 19 children with flat foot (9.32 ± 2.67 years) as the study group . Plantar pressures using footprints and pressure platforms have also been investigated.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Orthopedic insoles have been revealed to be an effective treatment for flatfoot by elevating the arch height and recovering the body weight supporting and force transmission [5]. Due to the difference between individuals (soft tissue material properties, flatness, etc.…”
Section: Introductionmentioning
confidence: 99%
“…Static and dynamic plantar pressure were measured during standing and walking in shoes using the Gaitview AFA-50 system (alFOOTs, Seoul, Republic of Korea), which includes a 700 × 500 × 45 mm active area, consisting of a 3 mm thick floor mat, comprising 2,304 (48 × 48) force-sensitive sensors; test time: changeable; maximum pressure: 100 N/cm 2 ; acquisition frequency: ≤ 86 images per second. In previous studies, this system demonstrated good to moderate reliability [19,20]. We used the twostep method.…”
Section: Assessment Proceduresmentioning
confidence: 99%